Reactivity and performance characteristics of mosaic lime mortars with different types of ceramic pozzolans - Μαντζάνα, Ελισάβετ (Πανεπιστήμιο Πελοποννήσου, 2018)
The purpose of the present research is the analysis of lime mortars as far as their ceramic pozzolans admixtures are concerned and has been mainly inspired by the technology of mosaic floors and cocciopesto mortars. The attention is focused on the reactivity and performance characteristics of ceramic materials once they are added into a lime mortar. The first part is composed by a brief presentation of mosaic floors, their construction materials and technology. Consequently, in situ mosaic conservation and new repair mortars requirements are discussed, in order to determine the context of that type of interventions. Finally, the theoretical part is completed with a literature review of previous research works related to the subject. The part of experimental methodology is based into two types of clays, Metakaolin as reference material and an authentic mosaic mortar substrate sample. The chosen clays, a calcareous Agios Syllas and a non-calcareous Thrapsano come from areas of Crete. Ceramic substances were created by firing those clays in two different temperatures. Subsequently, seven lime mortar mixtures containing these ceramics in very fine particles were prepared and left to mature (LMtk, LTHRaw, LTH550, LTH700, LASRaw, LAS550, LAS700). The specific specimens, as well as the ancient sample, were tested for their pozzolanic reaction and their mechanical properties after 28 days and then again after 6 months of maturation. The analysis was carried out with Thermal analysis, XRD, SEM/EDS, water absorption, compressive strength and 3 point bending test. The results indicate differences between the calcareous and non-calcareous ceramic admixtures concerning their pozzolanic reactivity and that is also reflected on their mechanical properties. Furthermore, useful conclusions were derived from their firing process, since there are differences between ceramics fired in 700o C and 550-580o C.
Keywords: Δάπεδα, Ψηφιδωτά -- Ελλάδα; Αρχαιολογική χημεία -- Μεθοδολογία; Δάπεδα, Ψηφιδωτά -- Τεχνική; Δάπεδα, Ψηφιδωτά -- Συντήρηση και αποκατάσταση -- Ελλάδα; Ψηφιδωτά δάπεδα; Τεχνική; Συντήρηση και αποκατάσταση αρχαιοτήτων; Αρχαιολογική χημεία